Metagenomic resolution of microbial functions in deep-sea hydrothermal plumes across the Eastern Lau Spreading Center - Anantharaman, Karthik; Breier, John A; Dick, Gregory J (ISME JOURNAL, 2016)
Microbial processes within deep-sea hydrothermal plumes affect ocean biogeochemistry on global scales. In rising hydrothermal plumes, a combination of microbial metabolism and particle formation processes initiate the transformation of reduced chemicals like hydrogen sulfide, hydrogen, methane, iron, manganese and ammonia that are abundant in hydrothermal vent fluids. Despite the biogeochemical importance of this rising portion of plumes, it is understudied in comparison to neutrally buoyant plumes. Here we use metagenomics and bioenergetic modeling to describe the abundance and genetic potential of microorganisms in relation to available electron donors in five different hydrothermal plumes and three associated background deep-sea waters from the Eastern Lau Spreading Center located in the Western Pacific Ocean. Three hundred and thirty one distinct genomic `bins' were identified, comprising an estimated 951 genomes of archaea, bacteria, eukarya and viruses. A significant proportion of these genomes is from novel microorganisms and thus reveals insights into the energy metabolism of heretofore unknown microbial groups. Community-wide analyses of genes encoding enzymes that oxidize inorganic energy sources showed that sulfur oxidation was the most abundant and diverse chemolithotrophic microbial metabolism in the community. Genes for sulfur oxidation were commonly present in genomic bins that also contained genes for oxidation of hydrogen and methane, suggesting metabolic versatility in these microbial groups. The relative diversity and abundance of genes encoding hydrogen oxidation was moderate, whereas that of genes for methane and ammonia oxidation was low in comparison to sulfur oxidation. Bioenergetic-thermodynamic modeling supports the metagenomic analyses, showing that oxidation of elemental sulfur with oxygen is the most dominant catabolic reaction in the hydrothermal plumes. We conclude that the energy metabolism of microbial communities inhabiting rising hydrothermal plumes is dictated by the underlying plume chemistry, with a dominant role for sulfur-based chemolithoautotrophy.
Keywords: ROV Jason (Remotely Operated Vehicle)